Combination of acid phosphatase positivity and rimmed vacuoles as useful markers in the diagnosis of adult-onset Pompe disease lacking specific clinical and pathological features - Dolfus, Claire; Simon, Jean-Philippe; Landemore, Gérard; Leroy, François; Chapon, Françoise (Folia Neuropathologica, 2016)
Introduction: The clinical and histological presentations of the adult form of Pompe disease may be atypical. In such cases, identifying histological signs that point to the diagnosis would be crucial to avoid a delay in care. The aim of our study was to investigate the presence of rimmed vacuoles and acid phosphatase positivity in muscle biopsies of patients with late-onset Pompe disease. Material and methods: We retrospectively studied muscle biopsies of all cases of the adult form of Pompe disease diagnosed at the University Hospital of Caen. Three of these four cases showed atypical clinical signs, and diagnosis was established tardily based on family history or systematic analysis of acid maltase activity. Results: All biopsies showed some rimmed vacuoles. The acid phosphatase reaction showed positive inclusions and labelled vacuoles in biopsies of all patients. Conclusions: The presence of rimmed vacuoles and acid phosphatase positivity in muscle biopsy should suggest the diagnosis of the adult form of Pompe disease, this is decisive since effective therapy is available.